Sosialisasi Pemilahan Sampah Organik Di Desa Anjani Kabupaten Lombok Timur - Dwi Kusuma Purnamasari; M. Khairi Azhari; Bq Gia Atma Audia; Gardena Aulia Rizkika Yasmin; Rehanun Rehanun; Sulis Cahyadi (Jurnal Gema Ngabdi, 2026)
This community service program was conducted in Anjani Village, East Lombok Regency, aiming to improve community knowledge, awareness, and behavioral change in household waste management through organic waste segregation using Black Soldier Fly (BSF) maggot-based bioconversion. The main problem identified was the low level of waste sorting practices at the household source, resulting in high volumes of unmanaged waste being directly disposed of in landfills. The implementation method included socialization activities, formation of a pilot project group consisting of 30 households, distribution of organic waste bins, and continuous assistance and monitoring of waste segregation practices. Collected organic waste was processed using BSF maggot bioconversion technology at the local 3R Waste Management Center (TPS 3R). The results showed an improvement in community knowledge and awareness regarding waste segregation, as well as positive behavioral changes toward more responsible environmental management. The program also enhanced the efficiency of waste processing at TPS 3R and reduced the amount of waste sent to the landfill. This study demonstrates that the integration of educational approaches and simple BSF-based bioconversion technology is effective in supporting sustainable community-based waste management systems.